Combination of marine bioactive compounds and extracts for the prevention and treatment of chronic diseases - Ebrahimi, Belgheis; Baroutian, Saeid; Li, Jinyao; Zhang, Baohong; Ying, Tianlei; Lu, Jun (Frontiers in Nutrition, 2023)
Background: In recent years, marine-based functional foods and combination therapy are receiving greater recognition for their roles in healthy lifestyle applications and are being investigated as viable and effective strategies for disease treatment or prevention. Aim Of the Review: This review article presents and discusses the relevant scientific publications that have studied the synergistic and additive effects of marine-based nutraceutical combinations with anti-obesity, anti-inflammatory, antioxidant, and chemo-preventive activities in the last two decades. The paper presents the mechanism of action and health benefits of developed marine bioactive combinations and discusses the limitation of the studies and recommends alternatives. Furthermore, it highlights the factors for developing new nutraceutical combinations from marine bioactive compounds, and finally, proposes the direction for future studies. Key Scientific Concepts of Review: Combination of marine bioactive compounds affords synergistic or additive effects by multiple means, such as enhancing the bioavailability, boosting the bioactivity, and neutralization of adverse effects of compounds in the mixture. For the development of marine-based combinations as functional foods, there are key points for consideration and issues to address. Knowledge of the mechanism of action of individual compounds and their combinations, optimum ratio and dosing of compounds, and experimental models must all be taken into account. Strategies to increase the number and diversity of marine combinations, and further development of marine-based functional foods, are available. However, only a small number of marine bioactive combinations have been assessed, and these were mainly focussing on fish oil and carotenoid synergy. Therefore, more research and resources should be spent on developing novel marine nutraceutical combinations as functional foods.